The Influence of the Age of Local Government on the Characteristics of Local Governments on the Financial Performance of Local Governments in North Maluku Province - Rendhy; Hartaty Hadady; Suwito (Jurnal Economic Resource, 2022)
The purpose of the study was to find out and obtain empirical evidence about the size of local governments, the level of wealth of local governments, the level of dependence on the central government, the age of local governments, capital expenditures, and the findings of BPK influence the financial performance of local governments. This study uses quantitative research methods with 11 research objects. The data analysis method used in this study was multiple linear regression analysis with purposive sampling as the sampling technique. The data analysis method used in this study is SPSS software version 22. The results show that the size of the local government, the level of local government wealth, the level of dependence on the central government, the age of the local government, capital expenditure, and BPK findings affect the financial performance of local governments.